2003
DOI: 10.1111/j.1708-8208.2003.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading in the Maxilla Using Flapless Surgery, Implants Placed in Predetermined Positions, and Prefabricated Provisional Restorations: A Retrospective 3‐Year Clinical Study

Abstract: The study confirmed the feasibility of an immediate-loading treatment protocol in the maxilla, which included flapless surgery, implants and abutments placed in predetermined positions, and prefabricated provisional restorations. All failures occurred within the first 2 months of loading. The unchanged survival rate and the low average bone loss found during the following 34-month study period indicate a good long-term prognosis for the performed immediate-loading treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
168
0
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 6 publications
(7 reference statements)
7
168
0
12
Order By: Relevance
“…Los diferentes sistemas de conexión entre los implantes y la prótesis mediante los aditamentos protésicos que configuran la interfase implante-pilar han sido también estudiados y han demostrado su éxito en la carga inmediata 3,7,9 . Se ha demostrado que en los implantes con conexión externa las fuerzas oclusales axiales (verticales) y horizontales son transmitidas a la cresta ósea; mientras que en los implantes con conexión interna las fuerzas horizontales son transmitidas a la cresta ósea y las fuerzas verticales son absorbidas a la unión implante/pilar desarrollándose un sistema más fortalecido 21 .…”
Section: Diseño Prostodóncicounclassified
See 1 more Smart Citation
“…Los diferentes sistemas de conexión entre los implantes y la prótesis mediante los aditamentos protésicos que configuran la interfase implante-pilar han sido también estudiados y han demostrado su éxito en la carga inmediata 3,7,9 . Se ha demostrado que en los implantes con conexión externa las fuerzas oclusales axiales (verticales) y horizontales son transmitidas a la cresta ósea; mientras que en los implantes con conexión interna las fuerzas horizontales son transmitidas a la cresta ósea y las fuerzas verticales son absorbidas a la unión implante/pilar desarrollándose un sistema más fortalecido 21 .…”
Section: Diseño Prostodóncicounclassified
“…Se han realizado estudios que demuestran los buenos resultados de la carga inmediata en restauraciones parciales y unitarias en el maxilar superior mediante la inserción de implantes y su restauración provisional inmediata con un éxito acumulativo del 96% después de 1 año de seguimiento o del 91% a los 3 años [8][9] .…”
Section: Introductionunclassified
“…[3][4][5][6][7] Taking surgical protocols and patient management a step further, there has also been a growing interest in explor ing the potential of a fl apless surgical approach to minimise post-operative trauma and accelerate postoperative healing. [8][9][10] However, this approach can risk significant complications should the operator misinterpret the underlying hard and soft tissue anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…[26,17] The soft tissue response was very favorable in these studies owing to the presence of a provisional crown throughout the healing phase, which allowed the sculpting of the interdental papilla and the attached gingiva. [26,27,28] In this treatment, an initial insertion torque of at least 45 Ncm was reached. Although clinical studies on immediate single implant loading reported varying minimal insertion torques for immediate loading, the authors of this report adopted a threshold of 45 Ncm.…”
Section: Immediate Placement and Provisionalization Of Maxillary Postmentioning
confidence: 99%